Improving the Quality of Education Through Value Co-Creation: A Case Study on Technology-Based Study Programs - Chairunnisa, Puspita; Juwita, Silvia Ratna; Tamzil , Fachmi (Jurnal Locus Penelitian dan Pengabdian, 2025)
This study aims to improve the quality of education in technology-based study programs through a value co-creation approach. In the context of entrepreneurship education, value co-creation emphasizes active collaboration between students, lecturers, and institutions in creating meaningful learning experiences that are relevant to the development of digital technology. This research adopts a quantitative approach by distributing questionnaires to active students enrolled in entrepreneurship courses at Esa Unggul University, Jakarta, particularly those engaged in technology-based learning through e-learning, digital platforms, and online entrepreneurial activities. To enrich the understanding of learning dynamics, supporting data were also collected through Focus Group Discussions (FGD) with students and lecturers. Quantitative data were analyzed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method. The results show that value co-creation has a positive and significant influence on the quality of entrepreneurship education, student satisfaction, and entrepreneurial intention. Furthermore, education quality and student satisfaction significantly affect entrepreneurial intention, which in turn drives entrepreneurial behavior. The integration of technology in learning enhances student participation, strengthens collaborative engagement, and supports the process of joint value creation within a digital educational environment. These findings emphasize that active student involvement in technology-based learning, supported by responsive collaboration from lecturers, can enhance educational quality and foster entrepreneurial behavior. This study provides theoretical and practical contributions for the development of curricula, teaching strategies, and higher education policies that are more participatory, adaptive, and technology-oriented